Air-grown hybrid copper(i) halide single crystals: structural transformations and ultraviolet-pumped photoluminescence applications. Issue 5 (7th February 2022) - Song, Zhexin; Yu, Binyin; Meng, Lingqiang; Liu, Guokui; Dang, Yangyang
Abstract : Gua3 Cu2 I5 single-crystals and their light emitting diodes (LEDs) showed strong yellow photoluminescence characteristics. Abstract : Lead-free copper-based halide hybrid materials have emerged as a class of potential candidates for next-generation optoelectronic devices. In this work, we demonstrated that Gua4 Cu4 Br8 and Gua3 Cu2 I5 (Gua = CH6 N3 + ) single crystals have been successfully grown by slow evaporation methods in an ambient atmosphere. Interestingly, non-centrosymmetric Gua6 Cu4 I10 single crystals were formed on the basis of Gua3 Cu2 I5 induced by chiral ( R )- and ( S )-methylbenzylamine (MBA) cations. In particular, Gua3 Cu2 I5 exhibited a large Stokes shift of about 200 nm with a long PL lifetime of about 3835 ns and an absolute PLQY of about 72.04% at room temperature. More importantly, ultraviolet (UV)-pumped light-emitting diodes based on Gua3 Cu2 I5 single crystals exhibited strong photoluminescence characteristics at an emission peaking position of about 575 nm with high luminance. The above characteristics should provide guidance for further applications of lead-free hybrid single-crystalline optoelectronic devices.